Analisis Kesenjangan Performa Layanan – Harapan Konsumen pada Sebuah Usaha Pangkas Rambut di Malang - Nicko Nur Rakhmaddian; Granita Hajar; Muhammad Dzulfikar Fauzi; Desita Nur Rachmaniar; Bunga Pasha Maulidina (MAMEN: Jurnal Manajemen, 2023)
Mbois Barbershop is MSME that provides hair cutting services and has been affected Covid-19 pandemic. Coinciding with the new-normal era, one way to increase the income Mbois barbershop is generate consumer loyalty. Consumer loyalty can achieve by improving service quality performance. The purpose this research is to analyze Gap between service industry performance and service expectations at Mbois barbershop and determine service improvements for Mbois barbershop. The benefit this research increase consumer loyalty, which can result in an increase the number of consumers. The research stages consist of determining the number samples, collecting questionnaire data, validity, and reliability testing, calculating Gap value, analyzing Cartesian diagrams, and business improvement. A total of 30 samples were used with random sampling method. Validity testing was conducted using Pearson correlation moment method and reliability testing using Cronbach's alpha method. Gap analysis was conducted using Cartesian diagram method and Gap value calculation. The results showed that all physical evidence variables fell into quadrant two, making it a priority for improvement, especially for attributes such as healthier hair after receiving services, cleanliness after haircuts, and no itching after haircuts. The recommended improvements are purchase hair tonic, Haircut Cape, and Neck Paper Tissue. The attributes that need to be reduced from service performance are in quadrant four, which includes the skill workers in handling visitor's requests from the responsiveness variable and the workers' display visitors as priority from the empathy variable. Suggestions for further research include conducting servqual analysis with nine Likert scales to obtain more objective consumer assessment. The suggestion for implementing improvements is to consider the cost of repairs.